(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
Dermatophytic infections continue to contribute to the burden of superficial fungal infections, hence the need for alternative antifungal agents from natural sources. This study comparatively evaluated the efficacy of the crude extract of Cremini kigali mushrooms and its ZnO nanoparticles against selected dermatophytic fungi. Crude extracts were prepared by maceration and ZnO nanoparticles were synthesized using the green synthesis technique, and characterized. Antifungal activity against selected fungi isolates was assessed using agar well diffusion and broth microdilution. The proximate composition of the mushrooms revealed the presence of protein (28.00%), moisture (26.85%), carbohydrates (20.65%), crude fiber (11.50%), ash (9.00%), and crude fat (4.00%). The GC–MS spectral profile of the ethanol extract revealed the presence of diverse bioactive metabolites. Synthesis of ZnO nanoparticles was confirmed through UV spectroscopy with absorption band in the ultraviolet region at 350–380 nm. The FTIR spectrum revealed the presence of functional groups such as O-H, C-H, C=O, and C-N. TEM micrographs revealed the nanoparticles to be spherical in shape with a size ranging from 15 to 45 nm. At a concentration of 500 mg/ml, the antifungal efficacy of the nano-synthesized extract was higher, with the formation of inhibition zones measuring 27.00mm ± 2.00. Results obtained on the minimum inhibitory concentration and minimum fungicidal concentration revealed the antifungal efficacy of the crude extract on test fungi at a concentration of 31.25-6.25 mg/ml and 31.25 mg/ml respectively for the ZnO nanoparticles, indicating the enhanced antifungal efficacy of the nano-synthesized extract compared with the crude extract.